Prevention of umbilical outpouchings and mortality in pigs: Meloxicam, tying, cutting, and chlorhexidine versus amoxicillin or no treatment? A clinical field trial - Marie-Louise Hansen; Inge Larsen; Tina Birk Jensen; Charlotte Sonne Kristensen; Ken Steen Pedersen (Porcine Health Management)
Abstract Background Umbilical outpouchings (UOs) are common in Danish pigs. Neonatal antibiotics are therefore used with the hope of reducing umbilical infections and subsequently UOs. However, the effect of neonatal antibiotics on preventing UO has been the subject of mixed conclusions, and secondly, treating all animals with antibiotics might exacerbate the development of antimicrobial resistance. This study analysed the effects of different treatments on the prevalence of umbilical outpouchings and mortality from birth to nursery unit. All treatment was on the day of birth. The groups were: a negative control group, an antibiotic group receiving amoxicillin, and an experimental group where the piglets had their umbilical cord disinfected with chlorhexidine, followed by tying and clipping, and lastly, injection with meloxicam. The pigs were examined six weeks after weaning, and all pigs that died during the study were autopsied. Results There were 5494 pigs divided across the three groups. There were no statistically significant differences in UO prevalence between the groups: control 3.9%, antibiotic 4.2%, and experimental 4.0% (p = 0.87). The only variable affecting the prevalence of UOs in this study was sex with females being at higher risk. There were no statistically significant differences in mortality between the groups from birth until departure from the nursery unit: control 22.9%, antibiotic 21%, and experimental 21.4% (p = 0.33). The variables affecting mortality were sex, intrauterine growth restriction (IUGR), birth weight, and cross fostering. Males had higher odds of dying, as had piglets recorded with some degree of IUGR. Also, low birth weight increased the odds of dying for all weight quartiles compared to the fourth (the heaviest piglets > 1.6 kg), as well as cross fostering increased the odds ratio of dying. Conclusions This study found no significant differences in the prevalence of UOs and mortality following different treatments at birth. The study showed that the prevalence of UO and mortality was not reduced following the administration of amoxicillin or meloxicam in combination with disinfection and tying of the umbilical cord.